The Experience of Locomotor Training From the Perspectives of Therapists and Parents of Children With Cerebral Palsy - Pool, Dayna; Elliott, Catherine; Willis, Claire; Thornton, Ashleigh (Frontiers in Rehabilitation Sciences, 2021)
Objective: To explore the experiences of intensive locomotor training from the perspective of therapists, parents and children with cerebral palsy. Design: A qualitative study using semi-structured interviews was employed to capture perspectives following intensive locomotor training intervention. Data were analysed thematically, systematically coding and interpreted by grouping information into themes and sub-theme categories. Participants: Two children (GMFCS level IV n=1 and V n=1), 5 therapists, and 7 parents of children with high daily physical assistance and equipment needs participated in the study. Setting: A paediatric tertiary hospital. Results: All participants had completed all of the locomotor training sessions. Experiences of locomotor training were described with relation to the suitability of locomotor training with sub-themes of intervention length and time, engagement within sessions, importance of support and the utility of locomotor training beyond a research context. Motivation for participating in locomotor training was described in relation to the enjoyment of movement as well as for increasing activity level. The barriers and facilitators to participating in locomotor training provided environmental and personal factor subthemes. Finally, the outcomes from the intervention related to improvements in physical health, sleep, affect and emotion, and ambulation in daily activities. Conclusion: The experience of intensive locomotor training from the perspectives of children, parents of children who have high physical assistance and equipment needs and the therapists providing the intervention was described. Future studies should consider outcome measures beyond motor capacity to quantify the perceived extensive outcomes of interventions meaningful to families.